Pemberdayaan Petani Lokal melalui Inovasi Agribisnis Berbasis Kearifan Lokal di Era Digital - La Harudin; Nurmaya Nurmaya; Haerudin Tao (Journal of Humanities, Social Sciences, and Education, 2025)
Empowering local farmers is a strategic step in strengthening food security and economic independence for rural communities. In the digital era, agribusiness innovation emphasizes not only increased productivity but also the integration of local wisdom values ​​as the social and cultural foundation of agrarian communities. This literature review aims to analyze how digital technology-based innovation can strengthen the position of local farmers through an approach rooted in local culture and traditions. This research examines various sources from national and international journals from 2020–2025 that discuss the relationship between digital technology, sustainable agribusiness, and the preservation of local wisdom values. The study's results indicate that the integration of digital technology in agribusiness, such as the use of agricultural e-commerce, smart farming, and digital community platforms, can increase production efficiency and market access for farmers. However, the implementation of these innovations is more effective when accompanied by a humanistic approach that respects local traditions and strengthens the social role of farmers as guardians of agrarian culture. Thus, agribusiness innovation based on local wisdom is a crucial strategy in addressing the challenges of globalization and climate change, while simultaneously maintaining the socio-economic sustainability of rural communities.